2019
DOI: 10.1021/acsomega.9b01626
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activation of Persulfate by Meso-CoFe2O4/SiO2 with Ultrasonic Treatment for Degradation of Chlorpyrifos

Abstract: Magnetic mesoporous CoFe2O4/SiO2 (Meso-CoFe2O4/SiO2) composites were simply synthesized. On the basis of previous studies, optimum preparation conditions of their structure and physical properties can be readily determined. CoFe2O4 nanocrystals and their mesoporous structure were authenticated by low-angle and wide-angle X-ray diffraction, high-resolution transmission electron microscopy, scanning electron microscopy, element mapping, X-ray photoelectron spectroscopy, nitrogen adsorption isotherms, and so on. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 51 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…All products except P4 have been detected by HPLC-TOF-MS/MS in the combination of microwave and persulfate [27]. By comparing the energy barriers of these three pathways, the cleavage of the P 1 =O 21 bond was the most favorable, making it the optimal pathway, which was consistent with the experimental detection of a significant amount of P1 [26,27].…”
Section: Subsequent Reactions Of Im1-1(oh)supporting
confidence: 76%
See 2 more Smart Citations
“…All products except P4 have been detected by HPLC-TOF-MS/MS in the combination of microwave and persulfate [27]. By comparing the energy barriers of these three pathways, the cleavage of the P 1 =O 21 bond was the most favorable, making it the optimal pathway, which was consistent with the experimental detection of a significant amount of P1 [26,27].…”
Section: Subsequent Reactions Of Im1-1(oh)supporting
confidence: 76%
“…•− and •OH have strong oxidation effect on CPY degradation [25]. Xie et al found that CPY presents a rapid removal rate and almost completely degraded with the ultrasoundactivated persulfate process [26]. This study proposed that the removal mechanism of CPY could be divided into two possible degradation pathways.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…•− ), 16,17 ( • OH), 18,19 and (O 2 •− ), 20,21 •− is typically generated from persulfate (PS, S 2 O 8 2− ). Due to the excellent stability of PS, it can be activated in various ways, including heat, 12 microwave irradiation, 15,22 ultrasonication, 23 and transition metals. 24 Meanwhile, PS stably exists in the matrixes until it is activated for in situ chemical oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Check for updates chlorpyrifos with 99.9% [13], while CoFe2O4-rGO was used for methylene blue, methyl orange, and rhodamine B dyes with an efficiency of 89%, 64%, and 58%, respectively [14].…”
mentioning
confidence: 99%